Simultaneous Quantification of Mitochondrial Mature Frataxin and Extra-Mitochondrial Frataxin Isoform E in Friedreich’s Ataxia Blood - Wang, Qingqing; Laboureur, Laurent; Weng, Liwei; Eskenazi, Nicolas M.; Hauser, Lauren A.; Mesaros, Clementina; Lynch, David R.; Blair, Ian A. (Frontiers in Neuroscience, 2022)
Frataxin isoforms are undetectable in serum or plasma, and originally whole blood could not be used as a biomarker in brief therapeutic trials for Friedreich's ataxia because it is present in long-lived erythrocytes. Therefore, an assay was developed for analyzing frataxin in platelets, which have a half-life of 10-days. However, our discovery that isoform E is only present in erythrocytes, whereas, mature frataxin is present primarily in short-lived peripheral blood mononuclear cells (PBMCs), granulocytes, and platelets, means that both proteins can be quantified in whole blood samples. We now report a quantitative assay for both frataxin proteoforms in whole blood from healthy control and FRDA patients. The assay is based on stable isotope dilution coupled with immunoprecipitation (IP) coupled with two-dimensional-nano-ultrahigh performance liquid chromatography/parallel reaction monitoring/high resolution mass spectrometry (2D-nano-UHPLC-PRM/HRMS). The lower limit of quantification was 0.5 ng /mL for each proteoform and the assays had 100% sensitivity and specificity for discriminating between healthy controls (n=11) and FRDA cases (N=100 in year-1, N=22 in year-2,3). The mean levels of mature frataxin in whole blood form healthy control and FRDA patients were 7.5 1.5 ng/mL and 2.1  1.2 ng/mL, respectively. The mean levels of isoform E in whole blood form healthy control and FRDA patients were 26.8  4.1 ng/mL and 4.7  3.3 ng/mL, respectively. The mean levels of total frataxin in whole blood form healthy control and FRDA patients were 34.2  4.3 ng/mL and 6.8  4.0 ng/mL, respectively (Figure 4). The assay will make it possible to rigorously monitor the natural history of the disease and explore the potential role of isoform E in etiology of the disease. It will also facilitate the assessment of therapeutic interventions (including gene therapy approaches) that attempt to increase frataxin protein expression as a treatment for this devastating disease.